The Creative Process of Dance in Genye Art in Purwakarta District - Nurul Firdhausa; Ayo Sunaryo; Ria Sabaria (Gondang: Jurnal Seni dan Budaya, 2023)
The development of the times has always made the younger generation face modern art. Many of them also focus on continuing, preserving and developing the arts that were born in the community, so that they become meaningful arts. In the end, the art can function as a means of identity that strengthens human dignity and society. Genye art born in Purwakarta Regency, West Java, is still maintained, preserved and developed by artists and local communities. The creative process carried out departs from the previous form of presentation of the Genye Art performance by paying attention to aspects of choreography, makeup, clothing and property. The purpose of this research is to describe the creative process of dance with the development of Genye artistry in terms of choreography, makeup, clothing, and property. This research method uses descriptive analysis method with a qualitative approach. Data was collected by means of observation, interviews and documentation studies in the form of performance photos, photos of the development process and videos of Genye art that have been developed. The results showed that genye art underwent changes and development in terms of choreography which continued to change and develop, makeup and property from 2010 to 2023 at this time, which made this genye art continue to develop and be preserved to become the most prominent art in Purwakarta Regency. This research can provide motivation to artists and the community so that they can continue to maintain, maintain, preserve and develop the arts that were born and grow in their area, namely the arts that characterize the Purwakarta Regency, namely "Genye Art".